2005
DOI: 10.1016/j.laa.2005.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities for J-Hermitian matrices

Abstract: Indefinite versions of classical results of Schur, Ky Fan and Rayleigh-Ritz on Hermitian matrices are stated to J-Hermitian matrices, J = I r ⊕ −I n−r , 0 < r < n. Spectral inequalities for the trace of the product of J-Hermitian matrices are presented. The inequalities are obtained in the context of the theory of numerical ranges of linear operators on indefinite inner product spaces. We denote by σ ± J (A) the sets of the eigenvalues of A with eigenvectors x such that x * J x = ±1. We recall that a J -Hermit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…A numerical algorithm to draw the boundary of W J C (A) for an arbitrary A ∈ M n and C a J -Hermitian matrix is here presented. Theorem 2.1 and 1.1 of [1] provide the general principle. Our approach uses the elementary idea that ∂ W J C (A) may be traced by computing the supporting lines of W J C (A) as specified below.…”
Section: Numerical Algorithm and Examplesmentioning
confidence: 97%
See 2 more Smart Citations
“…A numerical algorithm to draw the boundary of W J C (A) for an arbitrary A ∈ M n and C a J -Hermitian matrix is here presented. Theorem 2.1 and 1.1 of [1] provide the general principle. Our approach uses the elementary idea that ∂ W J C (A) may be traced by computing the supporting lines of W J C (A) as specified below.…”
Section: Numerical Algorithm and Examplesmentioning
confidence: 97%
“…So there exists a line parallel to the imaginary axis separating σ J + (A) and σ J − (A). Then, by Theorem 1.1 of [1] tr(CU HU −1 ) : U ∈ U r,n−r = (−∞, a 0 ], a 0 = n j=1 c j λ j .…”
Section: Corollary 23 Let J C Be Under the Conditions Of Theorem 2mentioning
confidence: 99%
See 1 more Smart Citation
“…which was investigated for J -Hermitian matrices A, C under certain conditions [5,18]. For J = I n , W J C (A) is called the C-numerical range of A, and is simply denoted by W C (A).…”
Section: Introductionmentioning
confidence: 99%
“…In Theorem 2.1 of [5], it has been shown that if the eigenvalues of A are not all real, and assuming that c r > c r+1 , then W J C (A) is the whole real line. Notice that having in mind the inequality c 1 > c r+s , this constraint may be removed.…”
Section: Introductionmentioning
confidence: 99%